Energy audit of commercial buildings (a case study of global fleet oil ltd. and national mirror houses (2012)
"The dearth and cost of energy supply in Nigeria calls for planning and management through energy audit. The object of this paper is to carry out a comprehensive energy audit of the two commercial buildings commonly referred to as Energy House and Mirror House which are the head offices of the Global Fleet Oil & Gas Ltd. Company and National Mirror Newspaper respectively, using their 2011 energy consumption data. The power supplies to both offices are from the same generators which provide two third of the power supply to the building in 2011 but with different transformers of 1000 kV A each for the PHCN power supply. The facilities load were assessed by direct inspection and conversion were done where necessary. The capacities of the available three generators were 400, 640 & 1000 kW respectively (using 0.8 power factor) and the maximum load of the facility at any time in a day is 398 kW. This study has revealed the monumental financial waste on the un-utilized energy and facilities that could be replaced with energy saver equipment. Therefore, it is imperative that a holistic energy planning and regular assessment of energy requirements are considered as key components of building projects. "